The impact of corruption on economic growth on OECD countries - Linhartová, Veronika; Židová, Eva (Univerzita Pardubice, 2016)
The question if and how corruption can influence economic growth of countries is not answered by literature without controversies. One may thus encounter the view that corruption is "sand in the wheels" of the economy, which impedes economic transactions, as it reduces the security of property rights and contributes to inefficient allocation of resources. On the other hand, there are authors who believe that corruption is precisely what "greases the wheels" of the economy, because it allows individuals to avoid administrative and bureaucratic delays. Based on the searches results of the theoretical literature and empirical studies, this contribution verificates the validity of hypotheses about the negative impact of corruption on economic growth on a sample member states of the OECD in the period 1999 - 2014. Through information from the professional literature is for this purpose derived econometric model that provides a comprehensive overview of how corruption function in a selected sample of countries on economic growth. Econometric model proved that corruption negatively influences the economic growth, not only directly but also indirectly in selected group of countries. As the transmission channels through which corruption affects economic growth were confirmed household expenditures and net exports.
Keywords: corruption; economic growth; econometric analysis; transmission channel; Organization for Economic Cooperation and Development; D73; H11